2018
DOI: 10.18488/journal.aefr.2018.811.1365.1383
|View full text |Cite
|
Sign up to set email alerts
|

Do Board Characteristics Impact the Market Performance of Indian Banks?

Abstract: This paper explores the role of board characteristics of Indian banks on their market performance. We conducted panel data analysis on a sample of 29 Indian banks that form part of the National Stock Exchange (NSE) 500 index (covering a period of 8 years from 2009-2016). While ten board characteristics were considered as independent variables, Tobin"s Q was considered as the dependent variable (Tobin"s Q was assumed to be a proxy for market performance of banks). Findings suggest that only three out of ten boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…In higher innovativeness level it entails a weaker relationship between CL and Firm Performance. This finding support (O'Brien et al, 2003;Shukla, Sivasankaran & Dasgupta 2018) that small firms with a local CL tend to be at the lower end of the innovativeness scale. Surprisingly, innovativeness was not moderate the relationship between differentiation strategy and firm performance.…”
Section: Discussionsupporting
confidence: 77%
“…In higher innovativeness level it entails a weaker relationship between CL and Firm Performance. This finding support (O'Brien et al, 2003;Shukla, Sivasankaran & Dasgupta 2018) that small firms with a local CL tend to be at the lower end of the innovativeness scale. Surprisingly, innovativeness was not moderate the relationship between differentiation strategy and firm performance.…”
Section: Discussionsupporting
confidence: 77%
“…(2016) and Reguera-Alvarado et al(2017), who also revealed a positive association between gender diversity and performance. Though, this disputes the work ofAnkur et al (2018), who found a negative influence on performance. Looking at the ACEXP, increased audit committee expertise positively and significantly influences market performance.…”
mentioning
confidence: 60%
“…When assessing a firm's performance, different financial ratios such as return on capital employed (ROCE), return on assets (ROA) and return on equity (ROE) are applicable (Awinbugri & Prince, 2019). The measure of firm performance used was Tobin's Q, because it evaluates both the market values of the business and the book values (Ankur et al, 2018;Ojeka et al, 2019b), it is a widely known standard indicator of long-run company performance. The utilization of the market value of equity will identify the future growth prospects of the business that could occur from exogenous factors to managerial decisions (Shan & McIver, 2011).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Huang and Hillary (2018) employing a sample of 1,500 firms during the period 1998-2010, provide evidence for the positive impact of board characteristics on the ROA of firms. Shukla et al (2018) in their study on 29 Indian banks during the period 2009-2016, conclude that the board characteristics positively influence the market performance of the sample banks.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 93%